Speech and Language Therapy Degree: reflections about school admission criteria in Portugal and worldwide - Soares, Elsa Marta Pereira; Lima, Etelvina; Pinto, Carina; Franco, Débora; Salvador, Andreia; Lopes, Inês; Pós de Mina, Sónia (Revista de Investigación en Logopedia, 2022)
The purpose of the study is to identify the admission processes to the speech and language therapy degree worldwide and characterize how Portuguese speech and language therapists assess the candidates to the speech and language therapy degree. This is a descriptive, exploratory, and cross-sectional study. This study is divided into two studies. Questionnaires were used to collect data in both studies. The data were inserted and analyzed through descriptive statistics (via Statistical Package for the Social Sciences (SPSS) version 27) and content analysis. Considering study 1, the results show that there are no school admission criteria performed by a speech and language therapist in most countries. However, in some institutions, there are some specific procedures considering the acceptance of applicants to enter the speech and language therapy degree. Study 2 reveals that Portuguese speech and language therapists use mainly informal assessment procedures when performing school admission criteria. The skills/areas most valued as school admission criteria for accessing the degree are writing and reading skills. Most participants consider it essential to perform the school admission criteria before candidates can access the speech and language therapy degree.  There are different procedures worldwide considering the entrance in speech and language therapy degree. If school admission criteria should or should not exist is a matter of debate concerning inclusion and non-discrimination policies. Even in Portugal, where school admission criteria are mandatory, there is a high variability of procedures. All these results state the importance of discussing this matter in more depth, involving all the institutions and entities that formally represent the scientific area of speech and language therapy.
Keywords: graduate education; school admission criteria; speech therapy